Recurrent pericarditis in a patient with Bardet–Biedl syndrome: A case report - Mauro, Angela; Casini, Francesca; Congedo, Emanuele Chittano; L’assainato, Sara; Pinto, Francesca; Ansuini, Valentina; Mascolo, Ruggiero; Pedroli, Alice; Bernardo, Luca (Frontiers in Pediatrics, 2022)
Bardet-Biedl syndrome is a rare autosomal recessive disorder characterized by rod-cone dystrophy, renal dysfunction, obesity, learning difficulties, hypogonadism, polydactyl and many another minor features that can affect cardiovascular, locomotive, neurological and endocrine systems. We report a 16-year-old boy affected by Bardet-Biedl syndrome who presented recurrent pericarditis with an optimal response to treatment with Anakinra. To our knowledge, this is the first description of an association between Bardet-Biedl syndrome and recurrent pericarditis.